Mongolian Medicine Honghu-Qiqige Ethanol Extract Exhibits Anti-Inflammation Role in Arthritis - Li Gao Zhang, Ha Dan Bao; Wang, Xiu Lan; Enkhsuren, Enkhbold; Ba Tu, Bu Ren; Dorjbal, Enkhjargal; Damdinjav, Davaadagva (Central Asian Journal of Medical Sciences, 2021)
Objective: To explore the therapeutic effects of Honghu-Qiqige on collagen-induced arthritis (CIA) rats and the pharmacological mechanism. Methods: We evaluated the anti-inflammatory effect of Honghu-Qiqige’s ethanol extract on CIA, to our knowledge, for the first time. The level of pro-inflammatory cytokine was determined by an ELISA. The expression of TNF-α and IL-1β was analyzed by RT-PCR. Additionally, the expression level of NF-kBP65 was evaluated using the Western blot method. Results: Ethanol extract of Honghu-Qiqige significantly reduced the secretion of TNF-α and IL-1β in RAW264.7 cells stimulated by lipopolysaccharides. The expressions of IL-1β mRNA, TNF-α mRNA, and NF-kBP65 protein were inhibited in all dose ranges used (5, 20, and 50 μg/ml). The protective effect of the extract on RAW 264.7 macrophage inflammation induced by lipopolysaccharide was preliminarily confirmed, and the mechanism may be related to the NF-kBP65 pathway. The same results were obtained in vivo experiments. Conclusion: All these results suggest that Honghu-Qiqige ethanol extract has potential to develop drugs to treat arthritis.